Diagnóstico ambiental y plan de manejo del relleno sanitario de la ciudad de Zamora - Hidalgo Jiménez, Darwin Olmedo (2015)
The investigation was developed in the sanitary filler of Zamora's city, canton Zamora, county of Zamora Chinchipe, with the general objective of contributing to improve the final disposition of the solid residuals generated in the canton Zamora, the surface of the sanitary filler of Zamora's city is 4,75 ha, there is and its influence area is of 153 394,27 ha there is. In the phase of ordinary operation; impacts exist to the climate, and fairly significant impacts on the air provoked by emission of gases and bad scents, in the reciclaje press there is 69,8 dB (sound decibeles) that are superior to the established ones for the environmental norm. For the characterization of the flora you the sanitary filler traveled counting the different strata of vegetation, for the fauna our interviewed to the local population, as well as the direct observation of the present species in the filler. The identification and valuation of the environmental impacts was carried out with a checkup list, determined 11 environmental impacted factors, the womb of importance determined that the environmental factor of more impact negative is the air with 87 and the floor with 38 positive impacts in its restoration. Later on the plan of environmental handling was elaborated that includes the actions and strategies for the operation and closing of the sanitary filler that it allows us to avoid, to reduce and/or to mitigate the negative impacts that are generated during these stages.